A metal free electrocatalyst for high-performance zinc-air battery applications with good resistance towards poisoning species. (30th August 2020) - Najam, Tayyaba; Ahmad Shah, Syed Shoaib; Ali, Hassan; Song, Zhaoqi; Sun, Haohao; Peng, Zhengchun; Cai, Xingke
Abstract: The trace amount of poisoning species in air, such as SOx and NOx, greatly degrade the performance of zinc-air battery, as they block the active sites of conventional metal containing electrocatalysts. To overcome this challenge, a catalyst with enhanced electrocatalytic properties and good resistance towards the small molecular poisons should be prepared. In this work, we synthesized a P, N dual-doped porous carbon nanospheres (DDPCN), which showed an E onset and E 1/2 of 0.98 V and 0.87 V for ORR reduction in alkaline solution, and a Tafel slop of 72 mV/dec, over-performing all the other metal-free catalysts and comparable with the performance of state-of-the-art Pt/C (20 wt%). Moreover, the E 1/2 for DDPCN showed negligible change towards poisoning species; while the E 1/2 for Pt/C and typical CoOx /CNTs displayed 10/10 mV and 24/13 mV decay by adding trace amount of SO3 2− /NO2 − into the electrolyte solution. By using DDPCN as the electrocatalyst for zinc-air battery application, the device showed the highest open circuit voltage (1.48 V), the highest power density (224 mW cm −2 ) and the highest energy density (874 W h kg −1 ) among all metal-free catalysts, and their performances are even better than the Pt/C catalyst. Moreover, these performances showed negligible influence by the poisoning species for DDPCN based Zn-air battery, while the performances for Pt/C and CoOx /CNTs based Zn-air batteries were greatly deteriorated by the poisoning species up to 25% and 40%. Graphical abstract: Graphical illustration for structural resistance of DDPCN, CN, and CP for the incoming small molecules NOx and SOx . Image 1